Proceedings of the 1999 IEEE International Symposium on Assembly and Task Planning (ISATP'99) (Cat. No.99TH8470)
DOI: 10.1109/isatp.1999.782952
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary simulated annealing algorithm for optimizing robotic task point ordering

Abstract: High productivity requires that robot manipulators perform complex tasks in minimum time. This paper presents an Evolutionary Simulated Annealing (ESA) algorithm for optimizing an important class of complex tasks of point-to-point moves, such as mechanical assembly, electronic component insertion, and spot welding. This algorithm combines the basic principles of two major heuristic search methods: Simulated Annealing and Genetic Algorithms. Indeed, these methods are commonly used to solve the well-known Travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…If city1 < city2, P is set by formula (5). Otherwise P is set by formula (6). Where the new solution is P = c 1 c 2 c n .…”
Section: An Effective Sa Algorithm For the Tspmentioning
confidence: 99%
See 1 more Smart Citation
“…If city1 < city2, P is set by formula (5). Otherwise P is set by formula (6). Where the new solution is P = c 1 c 2 c n .…”
Section: An Effective Sa Algorithm For the Tspmentioning
confidence: 99%
“…At the same time, the TSP is an NP-complete problem, 14 whose computational complexity rises exponentially with the input size. Hence, it is advantageous to find suboptimal solutions with a reasonable cost in many of TSP applications such as vehicle routing, 9 data transmission in computer networks, 13 image processing and pattern recognition, 5 robot navigation, 6 and drilling problem. 8 The TSP can be understood as a search for the shortest closed tour that visits each city once and only once.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this research is to seek for an effective and efficient algorithm to optimise the design of curved roof surface. Some research has demonstrated the benefits of an evolutionary SA algorithm in searching for an optimal result (Barral et al, 1999;Loomis, 2001Loomis, , 2004. As genetic algorithm (GA) can offer designers a relatively quick means of identifying a selection of good solutions (Rafiq et al, 2003), it is expected to employ GA to make up the drawback of current algorithms built in the CATIA system.…”
Section: Introductionmentioning
confidence: 99%